SILVER JEWELLERY AND THE CULTURAL GRAMMAR OF ADORNMENT IN MARWAR - ETHNOGRAPHIC INSIGHTS FROM THE MEGHWAL COMMUNITY - Chaturvedi, Neekee; Mathur, Surbhi; Panwar, Tamegh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Silver jewellery in Marwar is not merely a decorative artform but a vital repository of cultural knowledge. By documenting its materiality, usage, and embedded meanings, the study aims to underscore that adornments serve as living artefacts of Marwar’s cultural legacy. This article presents a comprehensive documentation and cultural analysis of silver jewellery traditions in the Marwar region of Rajasthan specifically through the silver jewellery of the Meghwal community. Moving beyond the idea of jewellery as mere adornment, the study explores the multifaceted roles played by silver ornaments.